EFEKTIVITAS KINERJA DOSEN TERHADAP INOVASI AKSELERASI MAHASISWA GENERASI Z - Kadek Nonik Erawati; Anita Heptariza; Andreas James Darmawan (RISK : Jurnal Riset Bisnis dan Ekonomi, 2024)
This research explores approaches to educating generation Z (Gen Z) students with a focus on three basic algorithm components, namely lecturer acceleration, characteristic disruption, and generation Z students. Involving ages 19-23 years, generation Z students grow and develop in a dynamic technological environment, thus distinguishing them from previous generations with critical, creative and open thinking. Lecturers as learning facilitators are faced with significant challenges, including students' dependence on technology and difficulties in maintaining attention. In overcoming these obstacles, lecturers are expected to integrate technology effectively, design active and collaborative learning, and provide practical context for learning material. Learning methods that prioritize dialogue and collaboration are key, recognizing the important role of lecturer acceleration and the use of technology in achieving learning goals. This research uses a qualitative triangulation method involving in-depth interviews, document analysis, observation, and student surveys to produce six hypotheses that highlight the relationships between variables in the learning context of Generation Z students. Thus, this research contributes to understanding the complexity of the interactions between these factors. and its implications for the learning achievements of generation Z.